Nanoscopic structural rearrangements of the Cu-filament in conductive-bridge memories. Issue 29 (1st February 2016) - Celano, U.; Giammaria, G.; Goux, L.; Belmonte, A.; Jurczak, M.; Vandervorst, W.
Abstract : The electrochemical reactions triggering resistive switching in conductive-bridge resistive random access memory (CBRAM) are spatially confined in few tens of nm 3 . In this work, a combination of two- and three-dimensional scanning probe microscopy techniques are used to study the conductive filament formation, rupture and its nanoscopic structural rearrangements. Abstract : The electrochemical reactions triggering resistive switching in conductive-bridge resistive random access memory (CBRAM) are spatially confined in few tens of nm 3 . The formation and dissolution of nanoscopic Cu-filaments rely on the displacement of ions in such confined volume, and it is driven by the electric field induced ion migration and nanoscaled redox reactions. The stochastic nature of these fundamental processes leads to a large variability of the device performance. In this work, a combination of two- and three-dimensional scanning probe microscopy (SPM) techniques are used to study the conductive filament (CF) formation, rupture and its nanoscopic structural rearrangements. The high spatial confinement of our approach enables to locally induce RS in a confined area and image it in 3D. A conical shape of the CF is consistently observed, indicating that the ion migration is the rate limiting step in the filament formation when using high quality dielectrics as switching layers. The sub-10 nm electrical contact size of the AFM tip is used to study the filament's dissolution and detect the hopping conduction of Cu during the CF rupture. We consistently observe a tunnel gap formation associated with the tip-induced filament reset. Finally, aiming to match the fundamental understanding with the integrated device operations, we apply scalpel SPM to failed memory cells and directly observe the appearance of filament multiplicity as a major source of failures and variability in CBRAM.